2007
DOI: 10.1001/archpsyc.64.10.1189
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of an Association Between the Vasopressin V1b Receptor Gene (AVPR1B) and Childhood-Onset Mood Disorders

Abstract: We have found evidence to implicate the AVPR1B gene in the etiology of mood disorders, particularly in females. Antagonists of AVPR1b exhibit antidepressant qualities; hence, genetic variation in AVPR1B may have implications in HPA axis dysregulation in mood disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
52
4
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 67 publications
5
52
4
1
Order By: Relevance
“…The results herein were not congruent with other previously observed SNP associations on recurrent major depression (van West et al, 2004), panic disorder (Keck et al, 2008), and attentiondeficit hyperactivity disorder (van West et al, 2009), and a protective effect of a major allele haplotype in two of these studies (van West et al, 2004;van West et al, 2009). Our results most closely match those of Dempster et al (2007). Perhaps this may be explained by similar methods and outcomes: both Dempster et al (2007) and this study used family-based designs and therefore the associations were robust to population stratification, and childhoodonset major depression is an established endophenotype of suicidal behavior (Mann et al, 2009).…”
Section: Consortium 2010contrasting
confidence: 99%
See 4 more Smart Citations
“…The results herein were not congruent with other previously observed SNP associations on recurrent major depression (van West et al, 2004), panic disorder (Keck et al, 2008), and attentiondeficit hyperactivity disorder (van West et al, 2009), and a protective effect of a major allele haplotype in two of these studies (van West et al, 2004;van West et al, 2009). Our results most closely match those of Dempster et al (2007). Perhaps this may be explained by similar methods and outcomes: both Dempster et al (2007) and this study used family-based designs and therefore the associations were robust to population stratification, and childhoodonset major depression is an established endophenotype of suicidal behavior (Mann et al, 2009).…”
Section: Consortium 2010contrasting
confidence: 99%
“…In contrast to Dempster et al (2007), however, the associations were observed here without sex specificity. The results herein were not congruent with other previously observed SNP associations on recurrent major depression (van West et al, 2004), panic disorder (Keck et al, 2008), and attentiondeficit hyperactivity disorder (van West et al, 2009), and a protective effect of a major allele haplotype in two of these studies (van West et al, 2004;van West et al, 2009).…”
Section: Consortium 2010contrasting
confidence: 95%
See 3 more Smart Citations